Large Eddy Simulation of a supersonic lifted flame using the Eulerian stochastic fields method - Almeida,YPD; Navarro-Martinez,S (Proceedings of the Combustion Institute, 2019)
Scramjet propulsion systems can be the key to deliver the next generation of hypersonic planes. The high costs and complexity of gathering experimental data is a limiting factor in the development of such engine. In this context, numerical simulation has become increasingly popular to investigate supersonic combustion phenomena that otherwise would be prohibitively expensive. Despite recent progress, the simulation of high-speed compressible and reactive flows is still very challenging and presents many associated challenges. The chemical source term is highly non-linear and most combustion models are designed to operate in low-Mach number conditions. The present work investigates the use of Probability Density Function (PDF) in the context of Large Eddy Simulation models under supersonic conditions. Two approaches are considered: an extension of the joint scalar-enthalpy PDF for high-speed flows and a novel joint velocity-scalar-energy PDF model. Both formulations use the Eulerian stochastic fields approach implemented in a fully compressible density-based CFD code. The performance of the models are investigated in a supersonic lifted flame, comparing the stochastic formulations with traditional models that neglect sub-grid fluctuations. The results show that sub-grid contributions are important at coarse meshes and the stochastic fields approach can reproduce the experimental data and the scatter observed. The simulations suggest that the scalar-enthalpy PDF is the most robust formulations and the sub-grid closures of the joint velocity-scalar PDF need further investigation.